Religionskunskap i årskurs 9 - Rune Jönsson; Bodil Liljefors Persson (Educare)
Religious Education in year 9 of the Swedish Compulsory School: One part of the national Evaluation of Compulsory School conducted by the Swedish ministry of Education in 2003 deals with Religious Education (RE). It is based on the National Curriculum for RE and focuses on the perspectives of vital questions, faith and tradition and ethics. On basis of the results the authors suggest some directions for future teaching in RE. Concerning vital questions the pupil’s thoughts focus on the big life-issues. More than 70% often think of the meaning of life, the future and death. When asked to evaluate their RE, between 30% and 50% of the pupils state that they had discussed vital questions in class, but still they wish for more discussions.